IMPLEMENTASI GADAI TANAH DAN ATAU TANAH SECARA SYARIAH DI DESA CIBEUREUM KALONG KECAMATAN DRAMAGA KABUPATEN BOGOR JAWA BARAT - Rahmayanti Kiram; Ibdalsyah Ibdalsyah; Sutisna Sutisna (Kasaba, 2019)
The practice of pledge in Indonesian society is already a universal sociological phenomenon and occurs in almost all regions and develops from generation to generation. Similarly, in Bogor community in general and in particular the community of Cibeureum Kalong Village Bogor District, pawn is a common thing as well as a tradition from generation to generation that is often done by the people of the village. The practice of pledge that has been running without proof of documents, they carry out such mortgage transaction is only based on trust. Based on the formulation of problems and research objectives, the approach method used is a qualitative approach. The method used is between qualitative methods. Using qualitative research methods, qualitative descriptions of existing institutions exist within the community. Based on the research that the implementation of rice field ladang in the village of Cibeureum Kalong Sukawening Bogor district is still mostly done with customary law and pawnshops are not perfectly implemented, because in pawn transaction that has not been using the contract, they only use the contract verbally if any the proof is only a receipt, and there is no term period. As for the utilization of mahrum or collateral goods there is no profit sharing